MAGNETO HYDRODYNAMIC NATURAL CONVECTION FLOW ON A VERTICAL CYLINDER WITH A PRESENCE OF HEAT GENERATION AND RADIATION (Journal of Engineering, 2011)
The present work investigates the effect of magneto – hydrodynamic (MHD) laminar natural convection flow on a vertical cylinder in presence of heat generation and radiation. The governing equations which used are Continuity, Momentum and Energy equations. These equations are transformed to dimensionless equations using Vorticity-Stream Function method and the resulting nonlinear systemof partial differential equations are then solved numerically using finite difference approximation. A thermal boundary condition of a constant wall temperature is considered. A computer program (Fortran 90) was built to calculate the rate of heat transfer in terms of local Nusselt number, total mean Nusselt number, velocity distribution as well as temperature distribution for a selection of parameters setsconsisting of dimensionless heat generation parameter (0.0 ≤ Q ≤ 2.0), conduction – radiation parameter (0.0 ≤ N ≤ 10.0), and the dimensionless magneto hydrodynamic parameter (0.0 ≤ M ≤ 1.0). Numerical solution have been considered for a fluid Prandtl number fixed at (Pr=0.7), Rayleigh number (102 ≤ ≤ 105 ) l Ra . The results are shown reasonable representation to the relation between Nusselt number and Rayleigh number with other parameters (M, N and Q). Generally, Nu increase with increasing Ra, M, N and Q separately. When the MHD, N, and Q effect added to the heat transfer mechanism, the heat transfer rate increased and this effect increased with increasing in Ra, MHD, N, and Q. The effect of magneto hydrodynamic, heat generation and heat radiation on the rate of heat transfer is concluded by correlationequations. The results are found to be in good agreement compared with the results of other researchers.